You are Here: Home >< Maths

# C2 trig help watch

1. 1-sin^2x=sinxcosx
solve for valuew between 0 and 360
2. cos^2(x) + sin^2(x) = 1
3. yh i simplified that to cos^2x=sinxcosx
idk what to do next, if i divide by cos^2x i would get tanx=1 but I would lose a solution
4. (Original post by Mathlete18)
cos^2(x) + sin^2(x) = 1
yh i simplified that to cos^2x=sinxcosx
idk what to do next, if i divide by cos^2x i would get tanx=1 but I would lose a solution
5. (Original post by murat10q7)
yh i simplified that to cos^2x=sinxcosx
idk what to do next, if i divide by cos^2x i would get tanx=1 but I would lose a solution
The reason for that is because when dividing by cos^2(x) you are assuming that cos^2(x) is not equal to 0. So you need to also solve for the other case, namely that cos^2(x) does equal 0. Let me know if that helps
6. get everything on the left hand side... then you can factorize out the cosx...
7. (Original post by Mathlete18)
The reason for that is because when dividing by cos^2(x) you are assuming that cos^2(x) is not equal to 0. So you need to also solve for the other case, namely that cos^2(x) does equal 0. Let me know if that helps
Thanks I kinda understand but i dont know how to solve it.
8. (Original post by the bear)
get everything on the left hand side... then you can factorize out the cosx...
Yh thats what I did but i got cosx(cosx+sinx) =0 idk how cosx=-sinx is gonna help
9. (Original post by murat10q7)
Yh thats what I did but i got cosx(cosx+sinx) =0 idk how cosx=-sinx is gonna help
there should be a - in the bracket, not a plus.

so cosx = 0 or cosx = sinx... now you should be thinking about tanx....
10. (Original post by the bear)
there should be a - in the bracket, not a plus.

so cosx = 0 or cosx = sinx... now you should be thinking about tanx....
thanks i get it now cosx=0 tanx=1
11. (Original post by the bear)
there should be a - in the bracket, not a plus.

so cosx = 0 or cosx = sinx... now you should be thinking about tanx....
I think to solve this you to invade belgium
12. (Original post by murat10q7)
Yh thats what I did but i got cosx(cosx+sinx) =0 idk how cosx=-sinx is gonna help
This is basically the same principle as solving for a factorised quadratic:

If you have a*b = 0 then either a=0 or b=0 or both equal 0.

In this case a = cosx and b = cosx - sinx

Therefore the solutions are any solutions to cosx = 0 or cosx - sinx = 0

This is why if you have (x-a)(x-b)=0 the solutions are x = a and x = b because those are the respective values that makes one of the brackets equal to 0.

Does that make sense?
13. (Original post by Mathlete18)
This is basically the same principle as solving for a factorised quadratic:

If you have a*b = 0 then either a=0 or b=0 or both equal 0.

In this case a = cosx and b = cosx + sinx

Therefore the solutions are any solutions to cosx = 0 or cosx + sinx = 0

This is why if you have (x-a)(x-b)=0 the solutions are x = a and x = b because those are the respective values that makes one of the brackets equal to 0.

Does that make sense?
Yep makes perfect sense thanks

### Related university courses

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: March 22, 2017
Today on TSR

### He lied about his age

Thought he was 19... really he's 14

### University open days

Wed, 25 Jul '18
2. University of Buckingham
Wed, 25 Jul '18
3. Bournemouth University
Wed, 1 Aug '18
Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams